Внешнеэкономическая деятельность китайских предприятий - Мищенко, Владимир Акимович; Мозенков, Олег Владимирович; Лю, Бо (НТУ "ХПИ", 2014)
В статье рассмотрена внешнеэкономическая деятельность китайских предприятий, сферы интересов китайского капитала на международном рынке. Проанализирован размер инвестиций в зарубежные страны и перспективы дальнейшего развития инвестирования китайского капитала. Проведен анализ сотрудничества между Украиной и Китаем.

The article considers the foreign economic activities of Chinese enterprises, the scope of interests of the Chinese capital in the international market. Analyzed the amount of investment in foreign countries and the prospects for further development of Chinese capital investment. Analysis of cooperation between Ukraine and China.
Foreign economic activities of Chinese enterprises
Keywords: экономика; экспорт; капитал; economy; export; foreign economic activity; capital; enterprise